Genome-Wide Analysis of CDPK Family in Foxtail Millet and Determination of SiCDPK24 Functions in Drought Stress - Yu, Tai-Fei; Zhao, Wan-Ying; Fu, Jin-Dong; Liu, Yong-Wei; Chen, Ming; Zhou, Yong-Bin; Ma, You-Zhi; Xu, Zhao-Shi; Xi, Ya-Jun (Frontiers in Plant Science, 2018)
Plant calcium-dependent protein kinases (CDPKs) play important roles in plant growth. The data from drought-induced de novo transcriptomic sequences show that CDPKs are up- or down-regulated by drought to different degrees. In this study, 29 millet CDPKs were classified into four subgroups. These genes were unevenly distributed on 9 millet chromosomes, and chromosomes 2, 3 and 9 contained the most SiCDPK members. Analysis of putative cis-acting elements showed that most millet CDPK genes contained the ABRE, LTR, HSE, MYB, MYC, DRE, CGTCA-motif and TGACG-motif cis-acting elements, which are activated by abiotic stresses. Real-time PCR analysis indicated that 29 SiCDPK genes experienced different degrees of induction under drought and ABA stresses. SiCDPK24 had the highest expression levels at 6 h and 12 h of drought treatment and was chosen for further analysis. SiCDPK24 localized to the cell membrane and nucleus of Arabidopsis mesophyll protoplasts. Western blot analysis showed SiCDPK24 protein had autophosphorylation activity. Overexpression of SiCDPK24 in Arabidopsis enhanced drought resistance and improved the survival rate under drought stress, and it activated the expression of stress-related genes such as RD29A, RD29B, RD22, KIN1, COR15, COR47, LEA14 and DREB2A. These genes are involved in resistance to abiotic stresses in Arabidopsis. These results indicate that millet CDPK genes play important roles in resisting drought stress.